Some results on ordered filters of implicative semigroups - Young Bae Jun (International Journal of Mathematics and Mathematical Sciences)
We introduce a special set in an implicative semigroup. Using it, an equivalent condition of an ordered filter is stated. We prove that an ordered filter can be represented by the union of such sets.